Preprocedural coronary CT angiography significantly improves success rates of PCI for chronic total occlusion - Rolf, Andreas; Werner, Gerald S.; Schuhbaeck, Annika; Rixe, Johannes; Moellmann, Helge; Nef, Holger M.; Gundermann, Constantin; Liebetrau, Christoph; Krombach, Gabriele A.; Hamm, Christian W.; Achenbach, Stephan (International Journal of Cardiovascular Imaging, 2013)
Chronic total occlusions of coronary arteries occur in about 20 % of patients with suspected coronary artery disease and are more frequent with increasing age. The success rate of interventions is lower (55-80 %) compared to conventional lesions (>90 %). Coronary CT angiography (coronary CTA) provides information about the occluded segment, which cannot be obtained from invasive angiograms (XA). We therefore hypothesized that preprocedural coronary CTA may improve success rates of percutaneous coronary intervention (PCI) for coronary arteries (CTO). 30 patients with chronic total coronary artery occlusions (mean age 73 years, 26 men) and predicted high complexity were imaged by coronary CTA prior to PCI for CTO. CT data sets were acquired with a 64 detector row dual source scanner and retrograde ECG gating, 0.6 mm collimation and z-flying focal spot, yielding isovoxel spatial resolution of about 0.4 mm. Based on the CT data sets, established complexity criteria for CTO (Euro CTO club, Di Mario et al. in EuroIntervention 3(1):30-43, 2007) were evaluated and compared to invasive coronary angiography. Three-dimensional volume-rendered images of the occluded coronary artery were displayed in the catheterization lab during PCI to guide the advancement of the wire. PCI success, defined as the ability to advance the guide wire into the distal lumen with thrombolysis in myocardial infarction III flow was compared to 43 controls without coronary CTA using propensity score matching based on established criteria of procedural success. The course of the occluded segments was visualized by coronary CTA in all cases. Calcification, lesion length, stump morphology and presence of side branches were underestimated by invasive angiograms when compared to coronary CTA. PCI success rate in 30 patients who underwent pre-procedural CTA was significantly higher than in patients without prior coronary CTA [unmatched: CT 90 % (27/30) vs. no CT 63 % (27/43), p = 0.009; matched: CT 88 % (22/25) vs. no CT 64 % (16/25) p = 0.03]. Through information not readily seen on invasive coronary angiography, coronary CTA can significantly enhance success rates of PCI for CTO. © 2013 Springer Science+Business Media Dordrecht.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Chronic total occlusion; Coronary computed tomography angiography; PCI